2011
DOI: 10.1111/j.1745-4603.2011.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Texture Perception of Milk Desserts. I – Relationship With Rheological Measurements

Abstract: Studying and predicting consumers' texture perception of milk desserts are important for dairy companies during new product development and the design of positioning, advertising and communication strategies. In this context, the aim of the present work was to study the relationship between consumers' texture perception of milk desserts and rheological measurements. Six commercial milk desserts were evaluated by a panel of 50 consumers, who were asked to answer a check-all-that-apply question. The rheological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Moreover, as shown in Figure 5, consumers' perception of the term firm was correlated with apparent viscosity at 50 s _ 1 and G'. These results were in agreement with those published by other researchers (Ares et al, 2012;Janssen et al, 2007). Likewise, oral firmness, thickness and creaminess of desserts presented high correlation with yield stress values.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…Moreover, as shown in Figure 5, consumers' perception of the term firm was correlated with apparent viscosity at 50 s _ 1 and G'. These results were in agreement with those published by other researchers (Ares et al, 2012;Janssen et al, 2007). Likewise, oral firmness, thickness and creaminess of desserts presented high correlation with yield stress values.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…The JNDs that were finally calculated from the corresponding apparent viscosity at a shear rate of 50/s were related to the reference stimuli in a way so that the resulting Weber fractions were 0.16 (emulsions with constant X LBG and varying X F ) and 0.22 (constant X F , but varying X LBG ). Rheological properties at small deformation, especially the higher ratio of viscous to elastic contributions in emulsions with a higher X LBG (see Figure 3 ), may serve as a possible explanation for Weber fraction differences: results of multivariate analysis showed that a higher sensory creaminess is apparently linked to a lower loss tangent at small deformations for comparable systems [ 26 ]. Emulsions with varying fat content exhibit a lower tan δ and, as indicated by the viscosity related Weber fraction, can be distinguished more easily.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate thickeners/stabilizers for optimizing the viscosity of the product may also be used. They have direct influence on texture, which is a relevant parameter for yogurts and has been object of investigation in recent studies (Antmann et al, 2011;Ares, Budelli, Bruzzone, Gímenez, & Lema, 2011a).…”
Section: Comparison Of the Sensory Methodsmentioning
confidence: 99%